THE TRANSFORMATION OF INDONESIAN LANGUAGE LEARNING BASED ON DEEP LEARNING TO ENHANCE STUDENTS CRITICAL LITERACY - Erwin Ginting (Jurnal Penelitian Samudra, 2026)
The transformation of Indonesian language learning has become an urgent necessity in the digital era to address the persistent issue of low students’ critical literacy. Conventional instructional approaches are often insufficient in fostering higher-order thinking skills, analytical abilities, and reflective engagement with texts. This study aims to analyze the role and effectiveness of deep learning–based Indonesian language instruction in enhancing students’ critical literacy. The research employs a qualitative approach using a systematic literature review of scholarly articles, research reports, and educational policy documents published between 2020 and 2025. The findings indicate that deep learning–based instruction, which emphasizes conceptual understanding, meaningful learning, reflective thinking, and knowledge integration, significantly contributes to the improvement of students’ critical literacy, particularly in critical reading, argumentative writing, and discourse analysis. This study recommends the systematic integration of deep learning principles into Indonesian language learning as a strategic pedagogical approach to strengthening students’ critical literacy skills.